Evaluation of the Mechanical and Physical Behaviors of Flax Fiber‐Reinforced Polybutylene Succinate Biodegradable Composites in Packaging Applications - Sema Özalp; Sedef Sismanoglu; Ümit Tayfun; Carmen‐Mihaela Popescu; Fazilat B. Kairliyeva; Yasin Kanbur (SPE Polymers, 2025)
ABSTRACT Applying surface modification routes to natural fibers is a practical option for solving the incompatibility problem in polymeric composites. This study aimed to improve the properties of biodegradable and environmentally friendly polybutylene succinate (PBS) composites involving flax fiber (FF) with unmodified, alkalization, and silanization surface modification applied at 20 wt%. The surface modifications were successfully characterized by FTIR and SEM. The composites were prepared using a twin‐screw extruder followed by injection molding. The mechanical, thermal, thermo‐mechanical, wear, water absorption, biodegradation, and morphological properties were evaluated. The incorporation of FF improved the mechanical and thermal performance of PBS, while the surface modifications further increased the fiber‐matrix adhesion. In particular, the silanized FF provided water resistance due to the hydrophobic nature of siloxane and exhibited the lowest biodegradation rate under fungal exposure. In the case of silanized FF, a 5.4% improvement in tensile strength and nearly 3% of water absorption capacity were reached. Based on these outcomes, the silanized FF‐filled PBS composite was suitable for packaging applications where biodegradable, water‐resistant, and mechanically strong materials are required.